The poetics of time metaphors and blends in language and literature - Plata, Anna (Figurative thought and language,, 2018)
How does the concept of time, elusive and inconceivable as it may be, lend itself to verbal creativity? Is it possible to trace something like a "poetics of time"? This book embarks on this endeavor initiated by the assumption that verbal creativity can shed some new light on our understanding of time, challenging everyday linguistic patterns and manipulating mental representations in unforeseen ways. Drawing on empirical evidence from Modern Greek poetry, the book offers a unified account of time conceptualization along a continuum of various degrees of non-conventionality. It also shows, unlike what has been traditionally assumed in the literature, that creativity in the expression of time is not limited to metaphor but extends to other figurative tropes that are perhaps specific to poetry. Poetry thus transpires as an ideal testing frame for exploring temporal cognition and meaning construction alike.